Modulation of invasiveness and catalytic activity of Bordetella pertussis adenylate cyclase by polycations. - Raptis, A (1989)
Penetration of Bordetella pertussis adenylate cyclase into CHO cells was monotonically inhibited by polylysines, with a minimum degree of polymerization of greater than 6 and less than or equal to 9 to 10. Above this level, inhibitory potency per lysyl residue was independent of polymer length; 50% inhibition was obtained with 60 microM lysine monomer. Other polycations were also potent inhibitors. The adenylate cyclase itself showed a biphasic (stimulation-inhibition) response, with a similar independence of polymer length above a certain minimum. Half-maximal inhibitory concentrations for cyclic AMP accumulation corresponded to half-maximal stimulatory concentrations of poly-L-lysine for the cyclase. The inhibitory effect of polylysines on cyclic AMP accumulation was not reversed by washing or enzymatic removal of neuraminic acid. We conclude that charge-charge interactions play an important role in the penetration of B. pertussis adenylate cyclase into host cells.